Pseudomonas aeruginosa in children with cerebral palsy: a prospective study - Romaen, Katrien; Van Ussel, Isabelle; Van Rossem, Carolin; Kenis, Sandra; Ceulemans, Berten; Van Hoorenbeeck, Kim; Verhulst, Stijn (Frontiers in Pediatrics, 2023)
Children with cerebral palsy (CP) often present with chronic respiratory symptoms. Pseudomonas aeruginosa (PA), is a known pathogen associated with more severe respiratory disease. Preventive actions to eradicate this bacterium and to improve the respiratory condition of children with CP could be very valuable. Therefore, we assessed the prevalence of PA and its association with respiratory disease. Methods: Throat swabs were taken in children with CP, aged 0-18 years. Data from patient records were extracted from the electronic medical records. Follow-up of respiratory symptoms was done by the Liverpool respiratory symptom questionnaire (LRSQ) after 3 months. Results: A throat swab and a completed LRSQ after 3 months were received from 79 children with CP. Most children had a Gross Motor Function Score (GMFCS) of I (24.1%) and V (24.1%). Twentyeight patients (35.4%) were found to have at least one positive respiratory culture. Only 4 patients (5.1%) were contaminated with PA. Gram negative bacteria were isolated in 21.5% of the positive throat swabs, S. aureus was found in 13.9%. Most pathogens were found in patients with higher GMFCS score (GMFCS IV and V). Results of the LRSQ showed that 52.1% of these patients reported having 1 cold in the past 3 months. Discussion: The prevalence of PA in our population of children with CP is low, gram-negative bacteria were most commonly found. The respiratory consequences of being colonized with these bacteria were limited. These results may have been affected by the COVID-19 pandemic. Further research is recommended.